Usefulness of centor score for diagnosis of group A streptococcal pharyngo-tonsillitis and prevalence of the disease in Malaysia from 2016 to 2017 - Muthanna, Abdulrahman Mansoor Mohammed (2017)
Pharyngo-tonsillitis is very common in general practice and most of the cases are caused by viruses. One of the causes of pharyngo-tonsillitis is group A streptococcus, which has a strong indication for antibiotic treatment. It is difficult to distinguish between streptococcal pharyngo-tonsillitis from non-streptococcal according to the clinical findings. Nevertheless, up to 90% of the patients with sore throat might be treated with antibiotic. Over prescribing of antibiotics has very serious health effects with severe reactions and may promote antibiotic resistance and add significantly to the cost of health care. In Malaysia, Upper Respiratory Tract Infection (URTI) makes up nearly 30% of cases in primary care. Studies have shown trends of inappropriate prescribing of antibiotics for URTI in Malaysian primary care. Centor scoring is a guideline based on a set of criteria that help to identify the likelihood of streptococcal infections in patients with a sore throat. It was conducted to guide physicians to appropriately prescribe antibiotics for adults with pharyngo-tonsillitis. This study aims to describe the epidemiological pattern, etiology and its antibiotic susceptibility, clinical manifestation, antibiotic prescription among adults with sore throat and validity of Centor score in diagnosis group A streptococcal pharyngotonsillitis at three primary care clinics in Sepang, Selangor, Malaysia during 2016 to 2017. This cross-sectional study was conducted on 215 patients aged 18 and above with sore throat as one of the complaints at the three primary care clinics during December 2016 until April 2017. Throat swabs were collected from the patients for culture and analysis. Data on clinical manifestations, demographic characteristics, clinical information and throat sample results were analyzed using Chi-square test, and descriptive statistics. From all the participants (42.3% male, 57.7% female), (18.6% smokers, 81.4% non-smokers), (62.8%Malay, 30.2% Indian, 5.1% Chinese, 1.9 % others), 6 isolates (2.4%) were identified as GAS including 50% of those were associated with Centor score of 3 (p < 0.001), 50% were associated with Centor score of 4 (p < 0.001), and 0% with Centor scores of 0,1 and 2. Centor criteria were clinical predictors that associated with group A streptococcal pharyngo-tonsillitis (p < 0.001). Pharyngo-tonsillitis was diagnosed in 130 (60.5%) of the total adult participants who complained with sore throat. Beta hemolytic streptococci and influenza A and B viruses were isolated from 37.1% and 3.8 % of total participants, respectively. Both Centor scores 3 and 4 had sensitivity of 50%, and specificity of 97.6% and 100%; respectively, positive predictive value 37.5% and 100%; respectively, negative predictive value 98.6% and 98.6%; respectively, positive likelihood ratio 20.5 and 50; respectively, negative likelihood ratio 0.5 and 0.5; respectively. The accuracy of Centor score 3 was 96.3% while the accuracy of Centor score 4 was 98.6%. Antibiotics were prescribed to 48 (22.3%) including 8.3% with group A streptococcus and 91.6% with non-group A streptococcus. A majority of prescribed antibiotics was associated with Centor scores of zero to one (75.0%). Antibiotic susceptibility testing revealed that all beta hemolytic streptococci isolates were susceptible to penicillin G, ampicillin, ofloxacin, cefepime, cefotaxime, ceftriaxone, vancomycin, and linezolid, but 40%, 2.4%, and 9.6% were resistant to tetracycline, clindamycin, and erythromycin, respectively. The current study has suggested that the Centor score is useful for diagnosis and decision making for antibiotic therapy of GAS pharyngo-tonsillitis leading to decrease the unnecessary antibiotic prescription, while achieving better levels of treatment.